Short learning programme provisioning in nursing: An evaluative case study - Deirdre Elizabeth van Jaarsveldt; Annemarie Joubert (Elsevier, 2018)
In support of lifelong learning and redressing past inequalities the provision of short learning programmes and courses was encouraged in South African Higher Education. A school of nursing responded by establishing an academy wherein a range of these programmes was developed and presented. In this article the effectiveness of the initiative is evaluated in comparison to the national purposes for short learning programmes envisioned by the Council on Higher Education. These are to: enable access to higher education; support continuing professional development and generate third stream income for higher education institutions. A single evaluative case study design was employed by use of in-depth individual interviews with academy management team members, as well as a document analysis. The findings indicated that the academy, having navigated complexity, succeeded to a large extent in achieving the purposes. The continuing professional development needs of a wide range of health professionals in different settings were addressed. Regretfully, professional nurses cannot yet earn continuing professional development points in South Africa. Enabling of access to higher education is context bound. Subcategory nurses, for example, are not yet accommodated and applicants for formal academic programmes still need to comply with institutional requirements. A steady third stream income is currently generated in support of scholarship development at the school. Considering that the academy originally aimed "to enable nurses to adapt to the first and third world realities in South African healthcare," it is advisable that this aspect be specifically explored. Keywords: Access, Continuing nursing education, Continuing professional development, Short learning programmes, Third stream income